2010
DOI: 10.3349/ymj.2010.51.5.692
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cytosolic Phospholipase A2, 15-Prostaglandin Dehydrogenase, and Cyclooxygenase-2 Expressions on Tumor Progression in Colorectal Cancer

Abstract: PurposeIn addition to cyclooxygenase-2 (COX-2) which is related to prostaglandin E2 synthesis, other enzymes such as cytosolic phospholipase A2 (cPLA2), microsomal prostaglandin E2 synthase-1 (mPGES-1), and 15-prostaglandin dehydrogenase (15-PGDH) have been suggested to be related to carcinogenesis of colorectal cancer (CRC). The aim of this study was to investigate the roles of cPLA2, COX-2, mPGES-1, and 15-PGDH in tumor progression.Materials and MethodscPLA2, COX-2, mPGES-1, 15-PGDH, and vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Cytosolic phospholipase A 2 (cPLA2) expression is decreased in NIH 3T3 cells treated with either aspirin or sulindac (Yuan et al, 2000) and in CRC cell lines (SW480, Colo320 and HT-29) when treated with low mM (2.5-10) concentrations of aspirin (Yu et al, 2003). This observation is intriguing given that cPLA 2 expression has been proposed to participate in intestinal tumorigenesis (eg (Lim et al, 2010) and refs therein). Law et al have indicated that (high mM concentrations of) salicylate (in Balb/MK cells) can inhibit the activity and phosphorylation of the mitogen activated protein kinase, p70 s6k independent of p38 MAPK, with a concomitant reduction in DNA synthesis, cell proliferation and in expression of proliferation associated proteins such as c-MYC, cyclin D1, and PCNA and led the authors to conclude that salicylate may act via the mTOR pathway (Law et al, 2000).…”
Section: Nsaids Signalling Pathways and Apoptosismentioning
confidence: 89%
“…Cytosolic phospholipase A 2 (cPLA2) expression is decreased in NIH 3T3 cells treated with either aspirin or sulindac (Yuan et al, 2000) and in CRC cell lines (SW480, Colo320 and HT-29) when treated with low mM (2.5-10) concentrations of aspirin (Yu et al, 2003). This observation is intriguing given that cPLA 2 expression has been proposed to participate in intestinal tumorigenesis (eg (Lim et al, 2010) and refs therein). Law et al have indicated that (high mM concentrations of) salicylate (in Balb/MK cells) can inhibit the activity and phosphorylation of the mitogen activated protein kinase, p70 s6k independent of p38 MAPK, with a concomitant reduction in DNA synthesis, cell proliferation and in expression of proliferation associated proteins such as c-MYC, cyclin D1, and PCNA and led the authors to conclude that salicylate may act via the mTOR pathway (Law et al, 2000).…”
Section: Nsaids Signalling Pathways and Apoptosismentioning
confidence: 89%
“…A recent study reported the association of a risk of lung cancer with an HPGD SNP (Wang et al, 2010). It is inversely correlated with VEGF expression in colorectal cancer (Lim et al, 2010). HPGD is down-regulated in gastric cancer (Thiel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…who found higher expression of COX2 in advanced-stage than in early-stage CRC. Also Lim et al [23], proved that increased COX2 expression was related to depth of invasion and advanced stage.…”
Section: Discussionmentioning
confidence: 99%